Polyherbal formulation: Concept of ayurveda - Parasuraman, Subramani; Thing, Gan Siaw; Dhanaraj, Sokkalingam Arumugam (Pharmacognosy Reviews)
Ayurveda is one of the traditional medicinal systems of Indian. The philosophy behind Ayurveda is preventing unnecessary suffering and living a long healthy life. Ayurveda involves the use of natural elements to eliminate the root cause of the disease by restoring balance, at the same time create a healthy life‑style to prevent the recurrence of imbalance. Herbal medicines have existed world‑wide with long recorded history and they were used in ancient Chinese, Greek, Egyptian and Indian medicine for various therapies purposes. World Health Organization estimated that 80% of the word’s inhabitants still rely mainly on traditional medicines for their health care. The subcontinent of India is well‑known to be one of the major biodiversity centers with about 45,000 plant species. In India, about 15,000 medicinal plants have been recorded, in which the communities used 7,000‑7,500 plants for curing different diseases. In Ayurveda, single or multiple herbs (polyherbal) are used for the treatment. The Ayurvedic literature Sarangdhar Samhita’ highlighted the concept of polyherbalism to achieve greater therapeutic efficacy. The active phytochemical constituents of individual plants are insufficient to achieve the desirable therapeutic effects. When combining the multiple herbs in a particular ratio, it will give a better therapeutic effect and reduce the toxicity. This review mainly focuses on important of the polyherbalism and its clinical significance.
Keywords: Ayurveda; panchamahabhutas; polyherbal formulation